Finite Non-Deterministic Automata for FaultDiagnostic in Power Systems - Linden, Ricardo; da Silva, Victor Navarro Araújo Lemos (INFOCOMP Journal of Computer Science, 2012)
This paper introduces an application based on finite non-deterministic automata for power systems diagnosis. Automata for the simpler faults are presented and the proposed system is compared with an established expert system.